Propiedades físicas de la tensión pasiva labial y lingual: análisis teórico y experimental - Jaramillo-V., Pedro María; Radi-L., Jose N.; Jimenez-V., Ivan Dario; Bermudez-A., Jaime Alberto (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The purpuse of this study is to evaluate the passive labial and lingual tension with a lipsometer and glosometer. The study was done in forty patients, twenty has open front bite and increasen lower facial height. The other group has no abnormalities. All the patients has cephalometric and dentoalveolar evaluation. The results indicated that there were no significant differences between both groups and behavior biomechanic was given by the phisic formula of stretching F=ICX There was only a little difference in the constant of streching between both groups. It was lower in the patients with open bite and this could he expalined by a more flexible tissue.